Avaliação do estado nutricional relativo ao selênio e da expressão gênica de selenoproteínas em pacientes com aterosclerose tratados com estatinas - Ferreira, Diana Quitéria Cabral (2010)
The aim of this study was to determine the effects of the use of rosuvastatin in patients with atherosclerosis, in relation to blood parameters of selenium and selenoproteins, and also observe possible changes in gene expression of selenoproteins in these patients. The sample consisted of 27 adult and elderly patients with a clinical diagnosis of coronary artery disease undergoing angioplasty, treated at Natal Hospital Center hospital, Natal, RN. Patients were treated with rosuvastatin 10 mg/day during four months. Anthropometric variables such as body mass index (BMI) and Waist circumference (WC) were measured before and after treatment, as well as lipid profile, blood glucose and liver enzymes (AST and ALT). The diet of the patients was also analyzed using 24-hour diet recall. We analyzed the concentrations of selenium in plasma and erythrocytes, and also the activity of Glutathione Peroxidase and gene expression by Real Time PCR of selenoproteins GPx1, SelP1 and SelN1. Patients had mean age of 61.0 ± 9.4 years, 59.3% were men and 40.7% were women. After four months of treatment there was significant reduction of CA and, according to BMI, most were overweight. The intake of macronutrients, cholesterol, polyunsaturated fatty acids, monounsaturated and saturated was adequate, but the energy and fiber intake was below the recommendations. Regarding the selenium intake was observed a high prevalence of inadequacy. As expected, after treatment with rosuvastatin, a significant reduction in total cholesterol, LDL and glucose, which was not observed for HDL. Selenium concentrations in plasma and erythrocytes showed no changes, keeping within the established cutoffs. We observed a significant increase in GPx enzyme activity and mRNA expression of GPX1 and SEPN1, but not for gene SEPP1. Thus, it was found that treatment with rosuvastatin did not reduce the expression of selenoproteins. More studies are needed to clarify the effects of rosuvastatin on gene expression of selenoproteins in patients with atherosclerosis